Analysis SWOT Quantitative Strategic Planning Matrix (QSPM) Integration Analytic Hierarchy Process - Berampu, Lailan Tawila; Taufiqurrahman, Taufiqurrahman; Agassi, Luthfiyah (Forum Kerjasama Pendidikan Tinggi, 2025)
This research aims to analyze and determine the best marketing strategy for Expressive Coffee in Pekanbaru using an integrated approach of SWOT (Strengths, Weaknesses, Opportunities, Threats), Analytical Hierarchy Process (AHP), and Quantitative Strategic Planning Matrix (QSPM). The study employs a mixed quantitative and qualitative methodology through a case-study approach involving 15 respondents, including the owner, coffee experts, and regular customers of Expressive Coffee. Results indicate that Expressive Coffee possesses significant strengths such as specialty-grade coffee beans, open bar service, comprehensive facilities, and strategic location. However, weaknesses include relatively high product pricing, limited promotional activities, and restricted parking space. Major opportunities identified involve the rising healthy lifestyle trend, increasing premium coffee consumption, strategic partnerships with local farmers, and positive customer reviews. Primary threats are intense competition from emerging coffee shops and shifting consumer preferences toward convenient coffee products. Based on the QSPM analysis, the recommended strategy is the SO (Strength-Opportunities) strategy, scoring the highest Total Attractiveness Score (TAS) of 14.40, which emphasizes leveraging internal strengths to optimally exploit market opportunities.